Peran Corporate Communication dalam Meningkatkan Citra Perusahaan - Novembriani Irenita; Dina Saraswati; Rini Setiawati (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
Along with the development of national and international flights, not many airlines are able to survive in competitive condition. Corporate communication is the top management division of PT. Sriwijaya Air tasked with carrying out planned and directed communication management functions both internally and externally. The purpose of the research is to identify and analyze the role and function of Sriwijaya Air corporate communication to survive in a tight flight services competitive situation. The method used was descriptive qualitative research. From the research result of corporate communication as a division that deals with all forms of communication, Sriwijaya Air has a considerable contribution to the process of forming corporate image in its internal communication task of communicating company policies from top management to the lowest so that communication is established in two directions. While external communication has the task of establishing communication with the media and work partners for promotional activities and new company policies.